2022
DOI: 10.1002/bab.2356
|View full text |Cite
|
Sign up to set email alerts
|

Targeted therapies in non‐small cell lung cancer and the potential role of AI interventions in cancer treatment

Abstract: Non-small cell lung cancer is the most prevalent lung cancer, and almost threefourths of patients are diagnosed in the advanced stage directly. In this stage, chemotherapy gives only a 15% 5-year survival rate. As people have varied symptoms and reactions to a specific cancer type, treatment for the tumor is likely to fall short, complicating cancer therapy. Immunotherapy is a breakthrough treatment involving drugs targeting novel immune checkpoint inhibitors like CTLA-4 and PD-1/PD-L1, along with combination … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 101 publications
0
3
0
Order By: Relevance
“…Additionally, cytokine-inducible Src homology 2-containing (CIS) protein, which is an important cytokine checkpoint upstream of IL-15 signaling, is induced by the addition of cytokines, achieving enhanced metabolic fitness and effector functions in CAR-NK cells ( 70 , 167 ). Other studies have revealed the positive effects of PD-1/PD-L1 and CTLA-4 blockade on NK cells ( 168 ).…”
Section: Combination Of Car-nk Cells Therapy and Immune Checkpoint Th...mentioning
confidence: 97%
“…Additionally, cytokine-inducible Src homology 2-containing (CIS) protein, which is an important cytokine checkpoint upstream of IL-15 signaling, is induced by the addition of cytokines, achieving enhanced metabolic fitness and effector functions in CAR-NK cells ( 70 , 167 ). Other studies have revealed the positive effects of PD-1/PD-L1 and CTLA-4 blockade on NK cells ( 168 ).…”
Section: Combination Of Car-nk Cells Therapy and Immune Checkpoint Th...mentioning
confidence: 97%
“…In several cancer types, programmed cell death ligand 1 (PD-L1) is upregulated in the tumor microenvironment (TME) and in immunosuppressive cells [ 115 ]. Preclinical tests have revealed that PD-L1-targeted CAR-NK cells exhibit specific antitumor effects against several in vitro tumor cell lines, and exhibit robust in vivo antitumor effects against triple-negative breast cancer [ 116 ], bladder cancer [ 117 ], and lung cancer [ 118 ]. Human epidermal growth factor receptor 2 (HER2)/erythroblastic oncogene B 2 (ERBB2) is often overexpressed in breast, gastric, esophageal, ovarian, and endometrial cancers [ 119 ].…”
Section: Nk Cell Engineeringmentioning
confidence: 99%
“…CTLA-4 is highly expressed on activated T cells where it competes with CD28 for binding to CD80 and CD86 expressed on APC (Figure 1) [19]. Consequently, the overexpression of CTLA-4 in the tumour micro-environment can act as a biomarker for prognosis and treatment of NSCLC [20]. Targeting CTLA-4 can prevent the immunosuppressive CTLA-4 binding mechanisms by diminishing the co-stimulatory binding of CD28.…”
Section: Modes Of Action For Immunotherapies 1immune Checkpoint Block...mentioning
confidence: 99%